Pengaruh Implementasi Green Accounting Dan Material Flow Cost Accounting Terhadap Sustainable Development - Dzahwana Adnan; Azolla Degita Azis; Muhammad Anwar Masruri (CV. ITTC INDONESIA, 2025)
The mining world is experiencing significant developments, this will certainly have good and bad impacts, such as environmental pollution which will affect the sustainability of the company. One solution to this bad impact is to implement green accounting and material flow cost accounting properly. This study was conducted to determine how much influence green accounting and material flow cost accounting have on sustainable development in mining sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period, totaling 81 companies. The data collection method used the purposive sampling method with the multiple linear regression analysis method, obtained a research sample of 12 companies for 3 years totaling 36 samples registered in the 2021-2023 period. This study uses secondary data obtained from the annual reports of each company obtained from the Indonesia Stock Exchange and the websites of each company. The analysis tool used in this study was SPSS version 26. The results of the study using multiple linear regression analysis showed that: (1) Green accounting has no influence on sustainable development, (2) Production costs in the Material flow cost accounting element have no influence on sustainable development, (3) Production results in the Material flow cost accounting element have an influence on sustainable development, (4) simultaneously Green accounting, Production Costs and Production Results have a significant influence on Sustainable Development.